Student's Behavior at Private School: A Case of Private School in Kathmandu Valley - Sherpa, Dawa; Baraily, Khagendra; Basnet, Hom Bahadur (Rupantaran: A Multidisciplinary Journal, 2020)
This study aims to dig out the student learning behavior from the private school and explore the conception about socialization along with indoor and outdoor activity launched by the private school. Ontologically, this study stands up on subjective and multiple realities. Epistemologically, participants view and behavior are sources of knowledge and can be grasped subjectively. Regarding to research design, interpretative phenomenology was chosen as qualitative approach. Five students (S1, S2, S3. S4 and S5) from one of the private schools which was selected from Kathmandu Valley. The result indicated that there is inter-mutual relationship between student's activity and structure of private school. The student's behavior was found to be the reflection of school domination and very much care about the learning environment created by private school. The student culture was highly shaped by the configuration of teacher, parents and, administration. The student culture is required to modify by inculcating structured environment and essence of global society.